Study on the biological mechanism of urolithin a on nasopharyngeal carcinoma in vitro. (31st December 2022) - Yang, Yang; Ren, Zhen-Zhen; Wei, Wu-Jun; He, Zhi-Long; Deng, You-Lin; Wang, Zhuan; Fan, Yu-Chun; Zhou, Jie; Jiang, Li-He
Abstract: Context: Urolithin A (UroA) can inhibit the growth of many human cancer cells, but it has not be reported if UroA inhibits nasopharyngeal carcinoma (NPC) cells. Objective: To explore the inhibitory effect of UroA on NPC and potential mechanism in vitro . Materials and methods: RNA-sequencing-based mechanistic prediction was conducted by comparing KEGG enrichment of 40 μM UroA-treated for 24 h with untreated CNE2 cells. The untreated cells were selected as control. After NPC cells were treated with 20–60 μM UroA, proliferation, migration and invasion of were measured by colony formation, wound healing and transwell experiments. Apoptosis, mitochondrial membrane potential (MMP), reactive oxygen species (ROS) were measured by flow cytometry, Hoechst 33342, Rhodamine 123, JC-1 staining and ROS assay methods, respectively. Gene and protein expression were measured by RT-qPCR and Western blotting assay. Results: RNA-sequencing and KEGG enrichment revealed UroA mainly altered the ECM receptor interaction pathway. UroA inhibited cells proliferation, epithelial–mesenchymal-transition pathway, migration and invasion with IC50 values of 34.72 μM and 44.91 μM, induced apoptosis, MMP depolarization and increase ROS content at a concentration of 40 μM. UroA up-regulated E-cadherin, Bax/Bcl-2, c-caspase-3 and PARP proteins, while inhibiting COL4A1, MMP2, MMP9, N-cadherin, Vimentin and Snail proteins at 20–60 μM. Moreover, co-treatment of UroA (40 μM) and NAC (5 mM) could reverse the effect of UroA on apoptosis-related proteins. Discussion and conclusions: RNA-sequencing technology based on bioinformatic analyses may be applicable for studiying the mechanism of drugs for tumour treatment.